BUILDING THE HOTEL BRAND ADVOCACY TO ATTRACT MORE VISITORS - bellen, yuni alfitri; Tuti, Meylani (ESENSI: Jurnal Manajemen Bisnis, 2024)
This research aims to determine the influence of influencer marketing, social media marketing, product quality, service quality on brand advocacy. In collecting and researching data, researchers used a quantitative-based research approach. Sampling was carried out using a purposive sampling method and data was collected from 255 respondents. Using structural equation models as a data analysis method with the help of smartPLS software. The results of the analysis show that there is a significant influence of social media marketing, product quality, and service quality on brand advocacy. Meanwhile, the results of the analysis from influencer marketing on brand advocacy are that the negative effect is not significant. The practical implication of the results of this research is that Adotel Hotel Jakarta should be able to determine influencers who match the content or passion uploaded on their social media according to the product being promoted.